2008
DOI: 10.1016/j.nbd.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exercise in aged Tg2576 mice alters neuroinflammation and improves cognition

Abstract: Exercise is a treatment paradigm that can ameliorate cognitive dysfunction in Alzheimer disease (AD) and AD mouse models. Since exercise is also known to alter the peripheral immune response, one potential mechanism for the cognitive improvement following exercise may be by modulating the inflammatory repertoire in the central nervous system. We investigated the effects of voluntary exercise in the Tg2576 mouse model of AD at a time-point at which pathology has already developed. Inflammatory mRNA markers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 48 publications
9
113
0
Order By: Relevance
“…However, given that Zhao et al (2015) report that five months of treadmill running by 12 month old mice, of the same strain, reduces soluble A␤42 protein, we may speculate that the exercise regime adopted by Xu et al (2013) was insufficient rather than the pathology being too far In 18 month old mice, no effect on plaque load but ↓ aˇ and app hippocampal mRNA ↓ Cell survival in 6 month old and no effect at 18 months ↑ BrdU + /NeuN + cells in 6 month old progressed for exercise to mediate an effect. Similarly, Parachikova et al (2008) found no effect on amyloid pathology in 15-19 month old Tg2576 mice housed with a running wheel for three weeks. Furthermore, housing of one month old triple transgenic mice with a running wheel for six months had no effect on A␤42 or p-Tau expression (Revilla et al, 2014).…”
Section: Ad Pathologymentioning
confidence: 90%
See 1 more Smart Citation
“…However, given that Zhao et al (2015) report that five months of treadmill running by 12 month old mice, of the same strain, reduces soluble A␤42 protein, we may speculate that the exercise regime adopted by Xu et al (2013) was insufficient rather than the pathology being too far In 18 month old mice, no effect on plaque load but ↓ aˇ and app hippocampal mRNA ↓ Cell survival in 6 month old and no effect at 18 months ↑ BrdU + /NeuN + cells in 6 month old progressed for exercise to mediate an effect. Similarly, Parachikova et al (2008) found no effect on amyloid pathology in 15-19 month old Tg2576 mice housed with a running wheel for three weeks. Furthermore, housing of one month old triple transgenic mice with a running wheel for six months had no effect on A␤42 or p-Tau expression (Revilla et al, 2014).…”
Section: Ad Pathologymentioning
confidence: 90%
“…For instance, soluble A␤42 protein is reduced in eight and 17 month old APP SWE /PS-1 E9 mice following five months treadmill running, however, plaque number is only reduced in the eight month old mice (Zhao et al, 2015). Similarly, three weeks of voluntary wheel running did not ameliorate amyloid pathology in 15-19 month old Tg2576 mice (Parachikova et al, 2008). Moreover, ten days of wheel running reduced mRNA expression of A␤ and APP but did not alleviate plaque load in 18 month old APP23 mice (Mirochnic et al, 2009).…”
Section: Optimum Exercise Conditions For Maximal Effectmentioning
confidence: 93%
“…In addition, P3 latency and amplitude might represent electrophysiological indices that can be used to identify elderly patients with aMCI when performing the task-switching paradigm. It is important to highlight that cardiorespiratory fitness has positive effects not only on normal aging, but also on age-related neurodegenerative diseases [38,48,78,87,88]. The current study found that these electrophysiological markers were associated with VO 2max in subjects with aMCI.…”
Section: Discussionmentioning
confidence: 51%
“…With regard to neurodegenerative diseases (e.g., MCI or AD), several non-human animal studies also found that aerobic exercise could decrease brain amyloid burden and pathogenic phenotypes, facilitate neuronal survivability and function modulated by BDNF, and improve cognitive performance in a transgenic mouse model of AD [85][86][87][88]. Recently, Baker et al [48] found that long-term aerobic exercise could effectively improve multiple tests of executive control (e.g., task switching) for individuals with aMCI, and suggested that such an exercise mode plays a protective role by attenuating progression of cognitive symptoms in aMCI, although the beneficial effects of exercise on cognitive functions were more pronounced for the aMCI women than aMCI men, despite comparable gains in cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…In old Tg2576 mice, access to a running wheel for 13 weeks improved memory to levels similar to nontransgenic animals (125). Other studies found that as little as 3 weeks' running in 15-19-month-old Tg2576 mice, a time point where significant AD pathology has begun, was able to improve spatial learning (129) and decrease level soluble forms of A beta (126). One month of running in young TgCRNDA mice resulted in decreased proteolytic fragments of APP and after 5 months decreased Ab plaques in cortex and hippocampus (3).…”
Section: Animal Studiesmentioning
confidence: 92%